"To Conclude, Women Are a Mistake"1—A Study of Serbian User Discourse on 4Chan's /Pol/ Board on Women within Political Ideology. Issue 2 (3rd April 2021) - Milanović, Boris
Abstract: 4Chan remains a compelling yet insufficiently explored phenomenon of the modern Internet. Through the years, it has developed an infamy, especially concerning its /pol/ subboard, for being a belligerent and potentially extremist online community. The subboard has developed a user base composed predominantly of males who, almost completely anonymously, through a giant number of daily posts, discuss issues in some way connected to politics. This has resulted in one predominant discourse on women and their roles in the political world, one marked by description of a presumed all-encompassing and crippling inferiority. This paper seeks to illuminate this discourse by performing discourse analysis on a database of posts made by Serbian /pol/ users. The analysis is described in three closely connected sections. The first focuses on the explicit framing of women in political roles. The second and third sections describe the discourse as it pertains to the lack of fitness women allegedly show through impersonal social relations and as intimate partners, which together construct a basis and influential linkage as subboard users argue that they are unfit for politics as well.